Emergence Delirium with Transient Associative Agnosia and Expressive Aphasia Reversed by Flumazenil in a Pediatric Patient. (1st June 2015) - Drobish, Julie K.; Kelz, Max B.; DiPuppo, Patricia M.; Cook-Sather, Scott D.
<x xml:space="preserve">Abstract</x> Multiple factors may contribute to the development of emergence delirium in a child. We present the case of a healthy 12-year-old girl who received preoperative midazolam with the desired anxiolytic effect, underwent a brief general anesthetic, and then exhibited postoperative delirium, consisting of a transient associative agnosia and expressive aphasia. Administration of flumazenil led to immediate and lasting resolution of her symptoms. We hypothesize that γ-aminobutyric acid type A receptor-mediated effects, most likely related to an atypical offset of midazolam, are an important subset of emergence delirium that is amenable to pharmacologic therapy with flumazenil.